2016
DOI: 10.1515/rnam-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

Fitting the SEIR model of seasonal influenza outbreak to the incidence data for Russian cities

Abstract: In this paper we present a computational algorithm aimed at fitting a SEIR populational model to the influenza outbreaks incidence in Russian cities. The input data are derived from the long-term records on the incidence of acute respiratory diseases in Moscow, St. Petersburg, and Novosibirsk. It is shown that the classical SEIR model could provide a satisfactory fit for the majority of employed influenza outbreak incidence data sets (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Figures 8 and 9 present total cases and total mortality rate, respectively, and Figure 10 Table 7. represents the validation of the MPL-ICA and ANFIS models for the period of [20][21][22][23][24][25][26][27][28] April. The proposed model of MPL-ICA presented promising values for RMSE and determination coefficient for prediction of both outbreak and total mortality.…”
Section: Training Resultsmentioning
confidence: 99%
“…Figures 8 and 9 present total cases and total mortality rate, respectively, and Figure 10 Table 7. represents the validation of the MPL-ICA and ANFIS models for the period of [20][21][22][23][24][25][26][27][28] April. The proposed model of MPL-ICA presented promising values for RMSE and determination coefficient for prediction of both outbreak and total mortality.…”
Section: Training Resultsmentioning
confidence: 99%
“…The SEIR models through considering the significant incubation period during which individuals have been infected showed progress in improving the model accuracy for Varicella and Zika outbreak [13,14]. SEIR models assume that the incubation period is a random variable and similarly to the SIR model, there would be a disease-free-equilibrium [15,16]. It is worth mentioning that SEIR model will not work well where the parameters are non-stationary through time [17].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, due to the growing influence of collective immunity on the dynamics of morbidity, the prognostic model of the spread of influenza in the USSR, which was used in 1970s at the Research Institute of Influenza [10], showed a decline in the accuracy of predictions and due to that reason was put out of service [11]. The calibration of influenza dynamics models to contemporary Russian ARI data [12] confirmed that in case when ARI incidence is the only type of data used for the calibration procedure, the forecasting accuracy becomes low [13], [14]. Also, the population immunity level might not be accurately assessed by such model calibration when it is treated as a free parameter [15].…”
Section: Introductionmentioning
confidence: 99%